Genomic divergence between the migratory and stationary ecotypes of Atlantic cod. Issue 20 (3rd September 2013) - Karlsen, Bård O.; Klingan, Kevin; Emblem, Åse; Jørgensen, Tor E.; Jueterbock, Alexander; Furmanek, Tomasz; Hoarau, Galice; Johansen, Steinar D.; Nordeide, Jarle T.; Moum, Truls
Abstract Atlantic cod displays a range of phenotypic and genotypic variations, which includes the differentiation into coastal stationary and offshore migratory types of cod that co‐occur in several parts of its distribution range and are often sympatric on the spawning grounds. Differentiation of these ecotypes may involve both historical separation and adaptation to ecologically distinct environments, the genetic basis of which is now beginning to be unravelled. Genomic analyses based on recent sequencing advances are able to document genomic divergence in more detail and may facilitate the exploration of causes and consequences of genome‐wide patterns. We examined genomic divergence between the stationary and migratory types of cod in the Northeast Atlantic, using next‐generation sequencing of pooled DNA from each of two population samples. Sequence data was mapped to the published cod genome sequence, arranged in more than 6000 scaffolds (611 Mb). We identified 25 divergent scaffolds (26 Mb) with a higher than average gene density, against a backdrop of overall moderate genomic differentiation. Previous findings of localized genomic divergence in three linkage groups were confirmed, including a large (15 Mb) genomic region, which seems to be uniquely involved in the divergence of migratory and stationary cod. The results of the pooled sequencing approach support and extend recent findings based on single‐nucleotide polymorphism markers and suggest a high degree of reproductive isolation between stationary and migratory cod in the North‐east Atlantic.